PENGERINGAN CHIP LENJERAN MENGGUNAKAN PEMANAS LAMPU HALOGEN DAN LAMPU PIJAR - Wahyudi Wahyudi; R. Mursidi Mursidi; Endo Argo Kuncooro (Universitas Sriwijaya, 2012)
The purpose of this research was to study drying process of lenjeran chip using halogen and incandescent lamp as the heat energy sources. Lenjeran is a mixture of minced fish and tapioca and formed into tube shape. Halogen and incandescent lamp were set to increase temperature in the oven to 45oC. Lenjeran chips were dried for 12 h. Temperature in the oven, relative humidity, voltage, electric current and sample weight were recorded hourly. For the initial sample moisture of 43.5+ 0.3%, drying using a halogen lamp required 6 h and 33 min to achieve targeted final moisture 9% while using the incandescent lamp required 7 h 14 min. The electrical energy consumption of halogen lamp was 1.09 kWh with the average of relative humidity 73,38 %, while the incandescent lamp was 1,28 kWh with the average of relative humidity 77,69 %.Keywords : lenjeran chip, drying, halogen lamp, incandescent Lamp